ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, PRICE, CUSTOMER CONFIDENCE ON THE DECISION TO PURCHASE NATURAL STONE AT CV RAINBOW PELANGI - Liana Liana; Thomas Stefanus Kaihatu (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
There is a gap between the need and availability of housing in Indonesia. With the increase in the growth of housing developments in Indonesia, the need for natural stone as a support to beautify the appearance of the interior, exterior of houses and gardens is also increasing. This study aims to analyze the influence of product quality, service quality, price, customer trust, on natural stone purchasing decisions. The results of this study are product quality, service quality, price, and customer trust have a significant positive effect on purchasing decisions. Service quality variable (X2) is the most influence to purchasing decision (Y) with coeffient value 0,56, and then follow with price (X3) with coeffient value 0.28, and follow with product quality (X1) with coefficient value 0,14, and customer trust with coefficient value 0.06.